SOCIAL AND ECONOMIC INFLUENCES ON THE FORMATION OF RELIGIOUS IDENTITY IN THE CONTEXT OF QURAN STUDIES - Mashduqi Rifai; M. Khairul Fikri (STAI Sebelas April Sumedang, 2023)
Abstract This study investigates the impact of socio-economic factors on the formation of religious identity in Muslim communities, with a focus on Qur'anic interpretation. Using a mixed-methods approach, the research combines quantitative surveys and qualitative interviews to explore how variables such as income, education, and community environment shape individuals' religious practices and their approach to interpreting the Qur'an. The results indicate that individuals from higher socio-economic backgrounds tend to adopt more flexible, contextual interpretations of the Qur'an, while those from lower-income groups are more likely to adhere to literal interpretations. Furthermore, the study reveals that social environments, including urban and rural settings and the extent of interaction with other religious groups, significantly influence religious tolerance and openness to pluralistic interpretations. Globalization and modernization also play a key role in shaping more inclusive religious identities. These findings contribute to a deeper understanding of the interplay between socio-economic conditions and religious identity, providing insights for both scholars and policymakers in the fields of religion and social science.